Transverse Tibial Bone Transport Enhances Distraction Osteogenesis and Vascularization in the Treatment of Diabetic Foot. Issue 9 (10th August 2022) - Ou, Shuanji; Xu, Changpeng; Yang, Yang; Chen, Ya; Li, Wenjun; Lu, Hanyu; Li, Guitao; Sun, Hongtao; Qi, Yong
Abstract: Objective: To investigate the effect of transverse tibial bone transport on the treatment of Wagner Stage 4 diabetic foot. Methods: From January 2017 to October 2019, a total of 19 patients with Wagner Stage 4 diabetic foot ulcers were recruited. All patients were treated with transverse tibial bone transport. A detailed follow‐up was carried out at 1 week, 1 month, 3 months, 6 months, and 1 year after surgery. The wound healing rate and the limb salvage rate at 1 year after the surgery were evaluated. Preoperative and 3‐month postoperative digital subtraction angiography (DSA) were obtained. The level of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), epidermal growth factor (EGF) and platelet‐derived growth factor (PDGF) before surgery and on 1st, 4th, 11th, 18th, 28 th, and 35th days after surgery were measured. Operation time, intraoperative blood loss, postoperative complications, visual analog scale (VAS) pain score, skin temperature, Semmes‐weinstein monofilament (SWM), and ankle brachial index (ABI) were also assessed. Results: The wound healing rate and the limb salvage rate were both 94.74% in the patients at 1 year after the surgery. DSA showed the thickening of the calf and foot arteries, clear visualization, and a rich vascular network. The levels of VEGF, bFGF, and PDGF on the 11th, 18th, 28 th, and 35th days after surgery were significantly higher than those before surgery ( p  < 0.05). The EGF level on the 18th, 28th, and 35th days after surgery was significantly higher than that before surgery ( p  < 0.05). Superficial wound complications occurred in one patient during the hospitalization. There was no movement area infection, skin flap necrosis, tibial fracture, loosening of the external fixator, or rupture in study. Conclusion: Transverse tibial bone transport can improve the blood circulation of the affected limbs, promote the healing of diabetic foot wounds, and reduce the amputation rate of the affected limbs. Transverse tibial bone transport can promote the healing of Wagner Stage 4 diabetic foot. Abstract : Imaging of a typical case.